If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(4 + 6x) = -4x + -24 (4 * -6 + 6x * -6) = -4x + -24 (-24 + -36x) = -4x + -24 Reorder the terms: -24 + -36x = -24 + -4x Add '24' to each side of the equation. -24 + 24 + -36x = -24 + 24 + -4x Combine like terms: -24 + 24 = 0 0 + -36x = -24 + 24 + -4x -36x = -24 + 24 + -4x Combine like terms: -24 + 24 = 0 -36x = 0 + -4x -36x = -4x Solving -36x = -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -36x + 4x = -4x + 4x Combine like terms: -36x + 4x = -32x -32x = -4x + 4x Combine like terms: -4x + 4x = 0 -32x = 0 Divide each side by '-32'. x = 0 Simplifying x = 0
| 24x^2-40x-56=0 | | 52/7-5/14 | | 18-5x-2=-4 | | 7-(m-2)=12 | | 20Q+800=100+Q | | (2x-5)(3x^2-4x+1)=0 | | z^2+10z+11=0 | | 5(x+6)+1=3-2x | | 5(6m+7)=-2-7m | | s-9/10=21/10 | | 2(3w-12+w)=640 | | -9p=-72 | | 1.96x^5-4x^2-16x-16=0 | | 7-7(1-7x)=8x | | p(x)=-2x+100x-25 | | s-7/10=13/10 | | 12y=13.2 | | 5x+1+3=8(3x+2)+7(2-3x) | | 7(2y+1)=3(7+5y) | | X+x+.11+x+.11+.38=10.32 | | (2x+10)=(2x-15) | | 2(w+20+w)=380 | | -(1+6n)=-152 | | 121=0 | | 18-[2+3(8-5)]= | | 8(2+2x)-6=90 | | (x-2)2+(y+6)2=25 | | 2(x-3)+9=2x+2 | | X+5x+13=140 | | 1/2x=121 | | 19-5x/2=33 | | Y=6(6)-2 |